THE IMPACT OF VOLUME FRACTION METAL/CERAMIC CONSTITUENTS ON CRITICAL BUCKLING TEMPERATURE OF FUNCTIONALLY GRADED PLATE - Gordana Bogdanović; Dragan Čukanović; Aleksandar Radaković; Vladimir Geroski (Applied Engineering Letters, 2017)
A thermal buckling analysis of functionally graded rectangular plates is presented. Mechanical and thermal properties of the functionally graded material, except Poisson’s ratio, are assumed to vary continuously through the thickness of the plate according to a power-law distribution of the metal and ceramic volume fractions. Formulations of equilibrium and stability equations are based on high order shear deformation theory including shape function. An analytical method for determination of critical buckling temperature is developed. Numerical results were obtained in МАTLAB software using combinations of symbolic and numeric values. The effects of power-law index and temperature gradient on mechanical responses of the plates are discussed and appropriate conclusions are given.